Pengaruh Fasilitas Terhadap Minat Berkunjung Wisatawan di Bayt Al-Qur’an Al-Akbar Kota Palembang - Oktarina; Rini; Munparidi (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
Palembang is the Province of South Sumatera which many tourist attractions, which is a religious tourism namely Bayt Al-Qur’an Al-Akbar. This research focuses on the Bayt Al-Qur’an Al-Akbar tourist attraction. This research aims to determine the influence of Facilities on the Interests of Visiting tourists to Bayt Al-Qur'an Al-Akbar. This research methods uses quantitative-descriptive with data  form  survey techniques to visitors Bayt Al-Qur'an Al-Akbar through questionnaires the sample of 100 respondents. The research data uses Multiple Linear Regression Analysis processed with IBM SPSS version 25. Based on the results the test hypothesis t partially variable Facilities has a positive relationship and has a significant influence on the interests of visiting tourists to Bayt Al-Qur'an Al-Akbar. The results of F test simultan variable independent together has a positive and significantinfluence on the interests of visiting tourists to Bayt Al-Qur’an Al-Akbar. Facilities with a regression coefficient to the interests visiting, that the facilities needs to be improved to attract visitors coming back to Bayt Al-Qur'an Al-Akbar.